2005
DOI: 10.2337/diabetes.54.6.1635
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring in Interstitial Subcutaneous Adipose Tissue and Skeletal Muscle Reflects Excursions in Cerebral Cortex

Abstract: Continuous glucose monitoring (CGM) is being explored using several types of glucose sensors. Some are designed for subcutaneous adipose tissue. It is important to determine to which extent these glucose fluctuations in different tissues reflect changes taking place in the central nervous system, where glucose sensing is thought to occur. We studied the ability of subcutaneous adipose interstitial fluid measurements to parallel glucose propagations in blood, muscle, and central nervous system (CNS) during hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 24 publications
1
27
1
1
Order By: Relevance
“…Furthermore, wireless telemetric CGM designs would avoid direct tethering and implant sub-cutaneous micromotion issues observed in this study (Helton et al, 2011). Lastly, human CGMs are recommended clinically to be best placed in subdermal adipose tissue in humans (Nielsen et al, 2005), a situation very unlikely in the murine model given lack of such analogous adipose in rodent skin. (Perez and Davis, 2008) All of these differences likely contribute to fluctuations observed in the implanted murine CGM sensor outputs (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, wireless telemetric CGM designs would avoid direct tethering and implant sub-cutaneous micromotion issues observed in this study (Helton et al, 2011). Lastly, human CGMs are recommended clinically to be best placed in subdermal adipose tissue in humans (Nielsen et al, 2005), a situation very unlikely in the murine model given lack of such analogous adipose in rodent skin. (Perez and Davis, 2008) All of these differences likely contribute to fluctuations observed in the implanted murine CGM sensor outputs (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…However, an animal study by Nielsen and colleagues clearly demonstrated that measurements in the subcutaneous interstitial fat corresponded very closely with measurements in the central nervous system (CNS). 8 To summarize, interstitial fluid glucose concentration may be a better measure of functional status during periods of low glucose than capillary glucose concentration.…”
Section: Interstitial Glucose and Cognitive Performancementioning
confidence: 99%
“…Periodic finger prick tests, are often used by diabetic patients for measuring their own blood sugar level, due to the fact that glucose levels in blood can change rapidly (2.25 mg dL −1 min −1 ), often failing to detect all hypoglycaemic and hyperglycaemic events (Ricci et al 2007) as compared to other kinds of glucose sensors were reported (Sanz et al 2007;Ahmed et al, 2005;Gerritsen et al 2000;Gifford et al 2006;Lam et al 2002;Nielsen et al 2005). These glucose sensors measure blood glucose level directly by invasive method.…”
mentioning
confidence: 97%